An Unusual Presentation of an Osteoid Osteoma in the Lunate Bone. Issue 7 (July 2017) - Breitenfeldt, Nicole; Liodaki, Maria E.; Mailänder, Peter; Stang, Felix
Abstract : Summary: An osteoid osteoma is a rare benign tumor of the carpal bones. It is extremely rarely found in the lunate bone in patients above 30 years of age. We present a case report of a 61-year-old man with an osteoid osteoma of the left wrist, which was masked by degenerative carpal bone disease and a comorbidity of an inflammatory bowel disease. The mainstay of imaging including plain radiographs, computed tomography, magnetic resonance imaging, and bone scintigraphy led to the clinical diagnosis of a lunatomalacia. The tumor was removed by coincidence during removal of the diseased lunate bone. Postoperatively, the patient was immediately free of pain and remained free at his 3 months postoperative follow-up.